Values-Based Leadership Approach In Managing Cultural Diversity In Islamic Educational Institutions - Surbakti, Andika Hariyanto (Transformation of Islamic Management and Education, 2024)
This study aims to examine the effectiveness of value-based leadership in the management of cultural diversity in Islamic educational institutions, with a focus on the application of the principles of justice, honesty, and deliberation. This study uses a qualitative approach with a case study type, involving in-depth interviews, participatory observation, and document analysis as data collection techniques. Through thematic analysis, this study found that leaders who place Islamic values as the foundation of decision-making show higher abilities in creating an inclusive and harmonious work environment. The results of the interviews showed that a value-based approach was able to build trust and openness among members of the organization. Leaders who consistently apply the principles of justice and deliberation also show greater effectiveness in managing intercultural conflicts. The implications of this study show that value-based leadership has an important role in supporting harmony and collaboration in a culturally diverse environment, while also contributing to improving organizational performance. Thus, this research provides valuable insights for Islamic educational institutions in designing a leadership model that is able to optimize the potential of human resources in a sustainable manner.